Specialised English: New Directions in ESP and EAP Research and Practice by Ken Hyland & Lillian L.C. Wong (2019): Routledge - MUHAMMAD, Anugrah Puspita Ayu; MUSTAKIM, Mustakim (Research and Innovation in Applied Linguistics, 2023)
The Book â€œSpecialised English: New Directions in ESP and EAP Research and Practice by Ken Hyland & Lillian L.C. Wong (2019): Routledgeâ€ is a must-read book for ESP and EAP researchers and practitioners. It consists of three main sections: 1) conceptualizing issues in specialized language use (five chapters), 2) focusing on texts (six chapters), and 3) focusing on practice (six chapters). This book addresses some challenges in teaching and researching ESP courses across disciplines (Enesi et al., 2021). For example, contextualizing ESP teaching as â€œworkplace Englishâ€ is currently demanding, thus allowing ESP curriculum developers to formulate and infuse English materials in the workplace (V. K. Bhatia & Bremner, 2012).